High-sensitivity cardiac troponin I predict death and hospitalization at 1 year in patients assisting for a suspected acute cardiovascular condition: prospective cohort in a middle-income country (2021)
ABSTRACT: Introduction and Objectives: High sensitivity cardiac troponin (Hs-cTn) are specific biomarkers of myocardial injury. Besides diagnostic purposes, its use has been recommended for risk stratification. Most studies have evaluated the role of Hs-cTn T in prognosis estimation but there are few studies evaluating the performance of Hs-cTn I. Methods: We prospectively included patients assisting with a suspected acute cardiovascular condition. All patients have a Hs-cTn I measurement. Telephone-based interviews were performed at 3, 6, and 12 months. Medical chart review, telephonic follow-up, and national statistical system were used for event adjudication. A multivariable analysis, Kaplan Meier curves, and Cox proportional-hazards regression model were performed. Results: We include 555 patients. Mean age was 63 years and 56.8% were male. The most frequent diagnosis after hospitalization were acute coronary syndromes (29.7%) and non-specific chest pain (28.6%). Hs-cTn I was > 99th percentile in 44.5% of cases. At 1 year the primary outcome occurred more frequently in Hs-cTn I > 99th percentile group (HR 1.99, 95% CI 1.5 – 2.64; p< 0.001 (Figure 1). We found a linear relationship between primary outcome and the first Hs-cTn I concentration (Figure 2). In multivariable analysis, Hs-cTn I > 99th was independently associated with the primary outcome (OR 2.25, 95% CI 1.27 – 3.98; p = 0.05). Conclusions: Beyond diagnosis use, Hs-cTn I has a relevant role in risk stratification of patients with suspected acute cardiovascular conditions. The first Hs-cTnI value obtained in the emergency room has an independent association with primary outcome at 1 year.